Pengaruh Bauran Pemasaran dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT Mitra Sumber Utama Bekasi - Tuti Alawiyah; Heksawan Rachmadi (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The purpose of this research is to analyze the relationship between marketing mix and servicequality on purchasing decisions, either individually or jointly. The study was designed using asurvey method with a correlational approach and the data obtained were analyzed statistically.The study was conducted at PT Mitra Sumber Utama Bekasi using a sample of 50 employees.The research data was collected by recording secondary data and using a Likert scalequestionnaire which was calibrated using item validity and reliability coefficient tests.Analysis of the data using the correlation regression method, by testing the requirements of theanalysis, namely the heteroscedasticity test and the normality test of the estimated error.Statistical calculations using the SPSS software program. The research results are as follows:First, the results of the study state that the marketing mix variable (X1) has a positive effect onpurchasing decisions (Y) both partially. And the coefficient of determination obtained is 0.343.This shows that the marketing mix variable (X1) affects the purchasing decision variable (Y) by34.3%, while the remaining 65.7% is influenced by other variables not examined in this study.Second, the results of the study state that the service quality variable (X2) has a positive effecton purchasing decisions (Y) partially. And the coefficient of determination obtained is 0.308.This shows that the service quality variable (X2) affects the purchasing decision variable (Y) by30.8%, while the remaining 69.2% is influenced by other variables not examined in this study.Third, the value of the determinant coefficient is 44%. This shows that the variable (marketingmix) (quality of service) affects the Y variable (purchase decisions) by 44% while the remaining56% is influenced by other variables not examined in this study.The implication of the results of this study is that purchasing decisions can be improved throughefforts to improve the marketing mix and service quality that is more conducive and even better